Exploring the therapeutic potential of “Zhi-Zhen” formula for oxaliplatin resistance in colorectal cancer: an integrated study combining UPLC-QTOF-MS/MS, bioinformatics, network pharmacology, and experimental validation - Li, Yongjing; Chen, Ke; Li, Qin; Liu, Qiaoli; Han, Huijie; Liu, Hui; Wang, Songpo (Frontiers in Medicine, 2025)
BackgroundChemoresistance is a critical factor compromising the survival of patients with colorectal cancer (CRC). The “Zhi-Zhen” formula (ZZF), a traditional prescription developed by Chinese national medicine masters, has been extensively used in clinical practice to treat gastrointestinal cancer. Notably, ZZF has the potential to enhance tumor sensitivity to chemotherapy. Although previous in vitro studies have demonstrated the efficacy of ZZF in overcoming chemoresistance in colorectal cancer (CRC), its precise molecular mechanisms remain poorly understood.Materials and methodsWe used an integrated approach of bioinformatics and network pharmacology to predict the potential active ingredients and targets of ZZF in alleviating chemoresistance. The top five active ingredients identified by degree in the network analysis were validated using mass spectrometry. We then established an oxaliplatin-resistant CRC cell model to explore the potential targets and regulatory mechanisms through which ZZF overcomes chemoresistance at the cellular level.ResultsNetwork pharmacology and bioinformatics analyses jointly identified 29 active compounds and 13 potential key targets of ZZF, associated with chemoresistance. Among these targets, the differential expression of CASP7 significantly affected the progression-free survival of patients with CRC. We established two oxaliplatin-resistant CRC cell lines and observed an upregulation of CASP7 expression in these resistant cells. Furthermore, ZZF increases the expression and activation of CASP7 in resistant cells, promoting apoptosis, and thereby ameliorating chemoresistance. Additionally, β-catenin knockdown led to an upregulation of CASP7 expression, whereas activation of the Wnt/β-catenin signaling pathway reduced CASP7 protein levels. ZZF decreases the activity of the Wnt/β-catenin signaling pathway by decreasing β-catenin transcription and nuclear localization.ConclusionZZF has potential clinical value in the treatment of chemoresistance in CRC by inhibiting the transcription and nuclear localization of β-catenin, thereby increasing the expression of CASP7 and enhancing the apoptotic response in chemoresistant CRC cells.